Alkali activated materials based on fluid catalytic cracking catalyst residue (FCC): Influence of SiO2/Na2O and H 2O/FCC ratio on mechanical strength and microstructure - Tashima, M. M.; Akasaki, J. L. [UNESP]; Melges, J. L P [UNESP]; Soriano, L.; Monzó, J.; Payá, J.; Borrachero, M. V. (Elsevier, 2013)
Reuse of industrial and agricultural wastes as supplementary cementitious materials (SCMs) in concrete and mortar productions contribute to sustainable development. In this context, fluid catalytic cracking catalyst residue (spent FCC), a byproduct from the petroleum industry and petrol refineries, have been studied as SCM in blended Portland cement in the last years. Nevertheless, another environmental friendly alternative has been conducted in order to produce alternative binders with low CO2 emissions. The use of aluminosilicate materials in the production of alkali-activated materials (AAMs) is an ongoing research topic which can present low CO2 emissions associated. Hence, this paper studies some variables that can influence the production of AAM based on spent FCC. Specifically, the influence of SiO 2/Na2O molar ratio and the H2O/spent FCC mass ratio on the mechanical strength and microstructure are assessed. Some instrumental techniques, such as SEM, XRD, pH and electrical conductivity measurements, and MIP are performed in order to assess the microstructure of formed alkali-activated binder. Alkali activated mortars with compressive strength up to 80 MPa can be formed after curing for 3 days at 65°C. The research demonstrates the potential of spent FCC to produce alkali-activated cements and the importance of SiO2/Na2O molar ratio and the H2O/spent FCC mass ratio in optimising properties and microstructure. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Alkali activated material; Mechanical properties; Spent FCC; Waste; Alkali activated; Alkali-activated mortars; Aluminosilicate materials; Electrical conductivity measurements; Fluid catalytic cracking catalyst; Properties and microstructures; Supplementary cementitious material; Agricultural wastes; Binders; Carbon dioxide; Compressive strength; Cracks; Microstructure; Mortar; Petroleum refineries; Portland cement; Sodium; Wastes; Fluid catalytic cracking